Incidence of Trocar (Port) Site Hernias after Laparoscopic Cholecystectomy-Study of 100 Cases - Kabir, Sheikh Firoj; Haque, Md. Anowarul (Bangladesh Journal of Anatomy, 2013)
DOI: http://dx.doi.org/10.3329/bja.v9i2.15283 Bangladesh Journal of Anatomy 2011 Vol.9(2) pp.110-112